2016
DOI: 10.1097/scs.0000000000002637
|View full text |Cite
|
Sign up to set email alerts
|

Microsurgical Replantation of a Two-Segment Total Scalp Avulsion

Abstract: Total scalp avulsion is a rare and severe injury that may be life threatening and can result in devastating disfigurement and psychological trauma. Microsurgical hair-bearing scalp replantation is considered the procedure of choice and should be performed by a skilled surgical team. Replantation of a multifragmented scalp is even rarer and shows random results. Only 2 patients have been reported, resulting in partial or total necrosis of implanted fragments. The authors describe the successful replantation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 16 publications
(19 reference statements)
0
7
0
Order By: Relevance
“…Of 704 initial results, 61 studies were selected for data analysis. 1 2 4 5 6 7 8 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 ( Fig. 1 ) Nine studies included sample sizes of five-or-more patients.…”
Section: Resultsmentioning
confidence: 99%
“…Of 704 initial results, 61 studies were selected for data analysis. 1 2 4 5 6 7 8 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 ( Fig. 1 ) Nine studies included sample sizes of five-or-more patients.…”
Section: Resultsmentioning
confidence: 99%
“…Replantation is a method of reconnecting tissue or limb followed by the application of microsurgical technique. The first successful scalp replantation was conducted by Miller in 1976 [ 1 ]. Reportedly, only a few cases of partial or total scalp amputation can be found in the trauma unit [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Scalp amputation can lead to severe injury, permanent hair loss and massive blood loss. Partial defects can be managed by local flaps or skin grafts, while complete detachment may require free flap or replantation, with consideration of ischemia time and blood supplies for scalp survival [ 1 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the next couple of years, Buncke et al 4 and others [5][6][7] also reported successful scalp replantations with vascular anastomoses, and the microsurgery treatment has become the standard of care. [8][9][10][11] In this article, we will present 6 cases of scalp amputation and discuss our experience.…”
Section: Introductionmentioning
confidence: 99%